KAJIAN LAYANAN PERBANKAN SYARIAH DALAM MENCIPTAKAN KEPUASAN NASABAH PENYIMPAN DALAM UPAYA MENGOPTIMALKAN KONDISI LIKUIDITAS - Savitri Dewi, Lely (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2018)
The Birth of the Law of the Republic of Indonesia No. 10 of 1998 concerning Amendments to the Law of the Republic of Indonesia No. 7 of 1992 concerning Banking has provided a huge opportunity for the growth of Islamic banks in Indonesia, both Sharia Commercial Banks and Sharia People's Credit Banks. However, what is unfortunate in this case is that not all people understand and are aware of the ins and outs of Islamic banking practices, so that Islamic banks still have to be vigorous again in conducting socialization and promotion to all people in order to be able to compete with conventional banks in particular who do business development by opening a Sharia Business Unit (SBU). In terms of raising bank funds, banks generally rely on third party funds from customers to support fund distribution activities. Related to this, of course, bank services to customers, especially in fund management activities, must prioritize customer satisfaction so that they are always motivated to deposit their funds in the bank, so that third party fund mobilization is able to compensate for optimal fund distribution which will ultimately improve its liquidity performance through the Finance to Deposits Ratio (FDR). This FDR is used to see how far financing to customers can offset the obligation to immediately meet its short-term debt to customers who want to withdraw their money that has been used by the bank to see the ability and vulnerability of a bank